2020
DOI: 10.3389/fmed.2020.00205
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Histology Might Be an Indicator for Enhanced Survival Benefit of Chemotherapy in Stage II Colon Cancer

Abstract: Background: It was a difficult question to identify candidates who would benefit most from adjuvant chemotherapy in stage II colon cancer because of the paucity of relevant conclusive clinical trial results. We aimed to assess if mucinous adenocarcinoma (MUA) could be an indicator for the efficacy of adjuvant chemotherapy in stage II colon cancer. Methods: Using SEER * Stat software V.8.3.5, eligible patients were then recruited from the SEER database. A χ 2 test was applied to compare the distribution of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The neo/adjuvant treatment of MAC neoplasms is challenging: an impaired response to treatment and a shorter survival of patients is reported in most of the studies [ 22 , 24 , 33 ]. Some reports have suggested that the response to treatment in lower-stage MAC patients does not differ from that of non-MAC patients [ 34 , 35 ], but basically all of the studies agree that, in advanced stages, the therapy response of MAC is lower regardless the chemotherapy combination used [ 22 , 24 , 33 ]. Several novel therapeutic options have also emerged lately, including immunotherapies [ 22 , 24 ], drugs targeting mucins [ 36 ], and the possible use of nanoparticle drugs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neo/adjuvant treatment of MAC neoplasms is challenging: an impaired response to treatment and a shorter survival of patients is reported in most of the studies [ 22 , 24 , 33 ]. Some reports have suggested that the response to treatment in lower-stage MAC patients does not differ from that of non-MAC patients [ 34 , 35 ], but basically all of the studies agree that, in advanced stages, the therapy response of MAC is lower regardless the chemotherapy combination used [ 22 , 24 , 33 ]. Several novel therapeutic options have also emerged lately, including immunotherapies [ 22 , 24 ], drugs targeting mucins [ 36 ], and the possible use of nanoparticle drugs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that mucinous adenocarcinoma is more likely associated with advanced stages in CRC and less responsive to chemotherapy, comparing to non-mucinous adenocarcinoma [ 57 , 58 ]. The prognostic value of the mucinous histological subtype remains controversial, and some studies, including a very recently published large population-based study, disclosed that there was no significant difference in survival between these two entities in stage II CRC [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more important for clinicians is the ability to segment large regions to classify tumors and metastatic growths as well as other tissue components like tertiary lymph nodes and vascular invasion into a tissue. While cell morphology and distribution are quite important markers for pathologists, tissue segmentations would provide them with details more useful to the prognostic indicators of patient health (Huang et al, 2020). Tissue segmentation algorithms utilizing U-net, res-net, or some combination of the two have been developed to identify regions of melanoma (Thomas et al, 2021), mask and classify lymph node metastases (Khened et al, 2021), and predict angiogenic blood vessel growth into cancerous tissue (Yi et al, 2018).…”
Section: Segmentationmentioning
confidence: 99%